Book Review: Putting marketing ideas into action - Ida Farida (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2002)
Judul: Putting Marketing Ideas Into Action Pengarang: Keith Hart Penerbit: Library Association Publishing, London Tahun Terbit: Cetakan Pertama, 1999 Reviewer: Ida Farida